Determination of Bronsted Acid Sites in Porous Aluminosilicate Solid Catalysts using Volumetric and Potentiometric Titration Method - A Purwaningsih, .- (IOP Publishing, 2019)
The Brønsted acid site was determined by using volumetric and potentiometric titration method. The result showed that the Brønsted acid sites of synthesized aluminosilicate using volumetric titration method are aluminosilicate-1: 0.5491; aluminosilicate-2: 0.5523; and aluminosilicate-3: 0.5772 mmol/g and using potentiometric titration method are aluminosilicate-1: 4.7087; aluminosilicate-2: 5.5739; and aluminosilicate-3: 8.1059 mmol/g. FTIR-pyridine also showed the same trend line, the Brønsted acid sites concentration increased by the increasing of Si/Al mole ratio. The results of the measurement using FTIRpyridine showed the Brønsted acid sites concentration of aluminosilicate-1; aluminosilicate-2; and aluminosilicate-3 were 0.0293; 0.330; and 0.0336 mmol/g, respectively. The Brønsted acid sites concentration of aluminosilicate was higher using volumetric titration and potentiometric titration methods than using the FTIR-pyridine method, but the trend line was the same, the higher Si/Al mole ratio, concentration of Brønsted acid sites increased.